Slip rate and rare large prehistoric earthquakes of the red river fault, southwestern China - Shi, Xuhua (2018)
The Red River fault is an important plate‐boundary fault that has played a significant role in the tectonic evolution of northern Southeast Asia. Nonetheless, its millennial slip rate and earthquake recurrence behavior are poorly constrained. Analysis of 5‐ and 30‐m‐resolution topography reveals right‐lateral offsets that range from 60 m to 24 km along its “mid‐valley” trace but none along its “range‐front” trace. This strongly implies that the range‐front fault has experienced very little lateral slip for millions of years, even though it is the geologically more significant fault. Stratigraphic and geomorphologic investigation of the mid‐valley fault within a small channel near Gasa yields a 14C‐based slip rate of 1.1 ± 0.4 mm/year, averaged over the last 30,000–50,000 years. Three‐dimensional paleoseismic excavation of colluvial wedges produced by collapse of shutter ridges into the channel shows that sudden dextral ruptures of the fault have occurred every 6,000 ± 1,000 years over the past 30,000 years. Two and possibly three large surface ruptures occurred in the past 13,500 years, and two previous ones occurred at 18,500 and 24,500 calendar years before present (cal yr BP). The oldest one in the section likely occurred at or a few 1,000 years before 29,800 ± 2,000 cal yr BP. The 3‐D extent of the colluvial wedges implies dextral offsets of ≥4.5 m, amounts that are consistent with the slip rate and recurrence interval. The evidence for low slip rate and rare large seismic events is consistent with the lack of large historical earthquakes along the fault and the low Global Positioning System (GPS)‐derived slip rate, but is much lower than widely cited geological slip rates.